Borophene-enhanced molecularly imprinted electrochemical sensor for green, highly selective, and ultrasensitive rimegepant monitoring - Unal, Beyza; Cetinkaya, Ahmet; Ozdemir, Fatma Budak; Uzunoglu, Aytekin; Unal, M. Altay; Bellur-Atici, Esen; Ozkan, Sibel A. (Pergamon-Elsevier Science Ltd, 2026)
Rimegepant (RIM), a recently approved calcitonin gene-related peptide (CGRP) receptor antagonist, has attracted considerable attention owing to its dual therapeutic role in the acute treatment and prevention of migraine attacks, favorable safety profile, low risk of hepatotoxicity, and convenient oral administration. Among various 2D materials, borophene has significant potential for electrochemical sensing applications owing to its superior metallic conductivity, which facilitates electron-transfer kinetics, and its high electrochemical surface area. These advantageous properties of a borophene-based molecularly imprinted polymer (MIP) electrochemical sensor, denoted as RIM/poly(3-TBA@ANI)/Borophene/MIP-GCE, were successfully used for the selective recognition and quantification of RIM. The proposed sensing platform combined the high conductivity and surface activity of borophene nanoparticles with the molecular recognition capability of MIPs, resulting in a synergistically enhanced electrochemical interface. The developed sensor exhibited an excellent linear response over the concentration range of 1 & times; 10-12 - 1.0 & times; 10-13M, demonstrating its remarkable sensitivity for trace-level detection of RIM. The practical applicability of the sensor was evaluated through recovery experiments conducted in pharmaceutical, biological, and environmental samples, yielding satisfactory recovery values and analytical accuracy. Furthermore, the selectivity of the sensing platform was investigated in the presence of potential interfering compounds and structurally related molecules. The results confirmed the presence of highly specific recognition sites within the imprinted polymer matrix and demonstrated the sensor's superior affinity for RIM compared with competing species. In addition to its analytical performance, the environmental sustainability of the proposed methodology was comprehensively assessed using four complementary green metrics. The obtained scores revealed a favorable environmental profile, highlighting reduced reagent and solvent consumption, low waste generation, and environmentally benign fabrication procedures associated with the developed sensing strategy. The RIM/poly(3-TBA@ANI)/Borophene/MIP-GCE sensor represents a highly sensitive, selective, reproducible, and stable electrochemical platform for the determination of RIM. The combination of borophene nanostructures with molecular imprinting technology offers a promising approach to developing next-generation electrochemical sensors for environmental monitoring and bioanalytical applications. Departing from conventional trial-and-error approaches, the sensor's specific recognition mechanism was guided at the atomistic level using quantum chemistry and molecular dynamics (MD) simulations. Density functional theory (DFT) calculations revealed that the primary functional monomer, 3-TBA, formed strong hydrogen bonds with the electronegative regions of the RIM template. In contrast, the auxiliary monomer, aniline (ANI), facilitated complexation via it-it stacking interactions at neutral surface areas. Radial distribution function (RDF) analyses derived from MD simulations conducted in the isothermal-isobaric ensemble structurally validated the formation of a thermodynamically stable, high-affinity pre-polymerization complex driven by this synergistic network.
Keywords: Rimegepant; Molecularly Imprinted Polymer; Few-Layered Borophene; Electrochemical Analysis; Real Samples; Green Metrics